Empowering Entrepreneurial Leadership: A Conceptual Framework for Innovation and Growth - Mathur, Shweta (Journal of Economics and Management, 2026)
This conceptual paper explores the critical relationship between organizational culture and entrepreneurial leadership, focusing on how fostering a culture of high achievement and innovation excellence empowers entrepreneurs to drive sustainable growth and competitive advantage. This research examines the most effective methods used by high-performing companies that foster an entrepreneurial culture by utilizing a conceptual framework grounded in qualitative research and backed by statistics from around the world, secondary sources and an extensive literature analysis. The findings highlight culture’s pivotal role as a competitive advantage in entrepreneurial settings. Organizations that nurture high-performing and innovative cultures experience greater resilience, agility and financial success. Leadership with vision, psychological safety, purpose alignment, learning continuously and employee empowerment are essential components. Techniques like design thinking, agile structures and innovation labs accelerate organizational innovation. This study provides practical insights and frameworks for entrepreneurs and business leaders to build scalable, values-driven, innovation-oriented environments. The implications extend to HR practitioners, startup incubators and policymakers fostering entrepreneurial ecosystems. Through the strategic prioritization of culture, entrepreneurs may propel expansion and prosperity. Future study avenues are suggested in the paper’s conclusion, including mixed-method techniques or longitudinal case studies for empirical validation. This study contributes to the understanding of organizational culture’s impact on entrepreneurial leadership, offering actionable recommendations for building high-achieving and innovative cultures.